2019
DOI: 10.1016/j.jcot.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

How effective is periarticular drug infiltration in providing pain relief and early functional outcome following total hip arthroplasty?

Abstract: The aim of the study was to compare the efficacy of periarticular injection of a cocktail of analgesic drugs (PIC) with epidural infiltration (EA), in providing postoperative pain relief and early functional improvement following Total Hip Arthroplasty (THA). Methods: 50 patients undergoing unilateral THA were randomized to receive either EA or PIC for postoperative pain control. Postoperative pain relief, as determined by the visual analogue scale (VAS), functional recovery and side effects related to EA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…et al Compared the two different ways of analgesia after THA, which were divided into the periarticular injection of a cocktail of analgesic drugs (PIC) and epidural infiltration (EA) group and epidural infiltration (EA) group. Finally, they found that the overall satisfaction of the PIC group was significantly better than that of the EA group ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…et al Compared the two different ways of analgesia after THA, which were divided into the periarticular injection of a cocktail of analgesic drugs (PIC) and epidural infiltration (EA) group and epidural infiltration (EA) group. Finally, they found that the overall satisfaction of the PIC group was significantly better than that of the EA group ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intraoperative PAI of multiple drugs has become an important procedure in perioperative pain control for total joint arthroplasty (TJA), a its efficacy has been proven by a series of studies. [ 18 , 27 , 28 ] PAI can also reduce opioid consumption, which results in a better postoperative experience, including improved satisfaction and rehabilitation. [ 29 , 30 ] However, research to date has largely focused on the use of PAI during hip arthroplasty performed as treatment for osteoarthritis or femoral head necrosis, and the effects of PAI in elderly patients undergoing THA for osteoporotic femoral neck fractures remained unknown.…”
Section: Discussionmentioning
confidence: 99%